O ponâtii "tekstovaâ norma" v kommunikativnoj stilistike teksta - Bolotnova, Nina S. (Stylistyka, 2021)
Communicative stylistics is a new field of modem functional stylistics and it is formed on the basis of other sciences, which study text as a fom1 of communication and phenomenon of idiostyle. In contrast to linguistics oftext and linguistic poetics communicative stylistics studies text in respect to author and addressee’s activity. Unlike pragmatics, psycholinguistics, psychopoetics, which are guided by the theory of speech activities, communicative stylistics concems linguistic-stylistic aspects of intercourse speech in their textual realization. And at the same time a research of structural and semantic text organization in the view of communicative effect is considered as analysis caused by some factors such as stylistic usage and author’s idiostyle. Activities approach in the context of communicative stylistics is connected with its examination as a fact ofinitial communicative author’s activity and an object of secondary communicative reader’s activity. The aim of communicative stylistics is to work up the problems of efficacy of author and addressee’s textual activity taking into account specific character of language person, field of intercourse, aim and tasks, genre and style peculiarities of text. In accord with anthropocentric approach to text idiostyle is considered as a dominant notion and it gets another communicative sense. This notion contains multifold demonstration of author’s language person in the structure, semantics and pragmatics of text. The ąuestions of normalization in text activity are considered as the main problem of communicative stylistics. A new aspect of this problem is that it is connected with efficacy intercourse of author and reader. Taking into consideration bilateral character of communication (initial and secondary communicative activity which is connected with text formation and text perception and interpretation) textual norm is regarded as an important factor for dialogic intercourse of author and addressee, which shows a standard of textual activ ity for a certain sphere of communication. Textual nom1 is defined as follows: 1 ) it is firm rules of textual activity which are prevalent historically and accepted by a society; standard texts for a certain sphere of communication are fom1ed on the bas is of these rules; 2) it is a system of communicative- pragmatic, genre and style, composition and speech norms, which is proper for a certain type of text and it shows its communicative essence, linguistic character and extralinguistic orientation; 3) it is a harmonious organization of all structural elements of text in accord with the basie idea of author and direction of attention toward addressee. This notion of textual norm takes into account a complex of the following factors: 1) place of text in the structure of universal model of speech communication by Roman O. Jakobson; 2) levels of model of language person which is out of text according to the theory of Yurij N. Karaulov; 3) communicative characteristics of speech which text must meet the requirements; 4) the main features and characteristics of text. ln spite of their stability textual nom1s are historically changed and varied depending on the type oftext (mainly it depends on its genre and style peculiarities, sphere of communication, literary school which author follows) and author’s intention and addressee’s factor.